2017
DOI: 10.1104/pp.17.01088
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Sucrose Transporters and Phloem Loading in Response to Environmental Cues

Abstract: Suc transporters (SUTs) play a key role in the allocation and partitioning of photosynthetically fixed carbon in plants. While a function could be assigned to many members of the SUT family, almost no information is available on their regulation. Here, the transcriptional regulation of SUTs in response to various environmental stimuli in the leaves of five dicots (Arabidopsis Extensive data on expression of SUTs in relation to changes of environmental conditions were obtained through a global analysis of 168 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
101
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(106 citation statements)
references
References 80 publications
4
101
0
1
Order By: Relevance
“…Gene expression was found to scale with phloem loading in response to certain abiotic stresses (5-7), but did not scale with phloem loading in response to increased light levels (7). In tomato, increased phloem loading under high-light conditions coincided with increased protein abundance of the phloem-loading SUC instead, indicating posttranscriptional regulation (7). Transcriptional and posttranscriptional regulation of the phloem-loading SUC was also observed in sugar beet in response to exogenously fed sucrose (8,9).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Gene expression was found to scale with phloem loading in response to certain abiotic stresses (5-7), but did not scale with phloem loading in response to increased light levels (7). In tomato, increased phloem loading under high-light conditions coincided with increased protein abundance of the phloem-loading SUC instead, indicating posttranscriptional regulation (7). Transcriptional and posttranscriptional regulation of the phloem-loading SUC was also observed in sugar beet in response to exogenously fed sucrose (8,9).…”
mentioning
confidence: 98%
“…This arrangement makes SUCs the most likely target of regulation. Indeed, recent analysis of phloem transport in response to environmental cues suggested that carbon export from leaves is directly linked to SUC activity (5)(6)(7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SUTs play a key role in the allocation and partitioning of photosynthetically fixed carbon in plants and therefore, if sucrose transport efficacy is promoted, the yield of plants could be further optimized. Moreover, high light could enhance photosynthesis, leaf sugar levels, and phloem loading; however, these factors do not influence SUT expression directly [48]. Thus, SUT overexpression under high light conditions could be an important component of increased plant yield phenotypes.…”
Section: Potential Role For Suts In Crop Field and Drought Resistancementioning
confidence: 99%
“…Further, previous studies have shown that regulation of SUTs is part of abiotic stress response (see e.g. (Gong et al, 2015)) and that both transcriptional and posttranscriptional mechanisms are involved in regulation of Suc export (Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%